2017
DOI: 10.5539/jas.v9n3p178
|View full text |Cite
|
Sign up to set email alerts
|

Natural Antioxidant Activity and Compounds Content from Wastes of Euterpe edulis Berries

Abstract: The Euterpe edulis (Juçara) is native to Brazil, which berries and wastes present high antioxidant content. Therefore, in this study, microwave-assisted extraction (MAE) was investigated for antioxidant compounds extraction from E. edulis waste and maximized antioxidant activities using response surface methodology coupled with a central composite design. Three factors were observed: microwave power (400/500/600 W), exposition time (30/60/90 sec) and ethanol concentration solvent (40/60/80%). The extracts were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
13
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(15 citation statements)
references
References 30 publications
2
13
0
Order By: Relevance
“…edulis waste extract, despite the use of the identical extraction parameters. This positive relationship between the concentration of phenolic compounds and antioxidant activity has been observed by other authors [15,36,37].…”
Section: Resultssupporting
confidence: 88%
See 3 more Smart Citations
“…edulis waste extract, despite the use of the identical extraction parameters. This positive relationship between the concentration of phenolic compounds and antioxidant activity has been observed by other authors [15,36,37].…”
Section: Resultssupporting
confidence: 88%
“…edulis extract (Table 1), which indicated that the pequi peel has higher concentrations of these compounds than the juçara waste (p<0.05). However, both extracts presented satisfactory levels of natural antioxidant compounds compared to other studies that used extraction conditions similar to our study [15,36].…”
Section: Resultssupporting
confidence: 71%
See 2 more Smart Citations
“…The liquid extract was obtained by microwave-assistant extraction using a DGT 100 Plus system (Provecto Analytics Ltd., Jundiaí, SP, Brazil) according to Frasao et al (2017), using a 94% aqueous ethanol solution (vol/vol) at 670 W microwave power for 110 s. Subsequently, the extract was concentrated in a rotaevaporator (Fisatom,model 801,Fisatom Scientific Equipment Ltd.,São Paulo,SP,Brazil) and then diluted to 6.25 mL/L, defined by the MIC reported by de Paula-Junior et al (2006) for Escherichia coli (6.25 μg/mL) and Staphylococcus spp. (4 μg/mL).…”
mentioning
confidence: 99%